Experimental determination of the electrostatic nature of carbonyl hydrogen-bonding interactions using IR-NMR correlations - Kashid, Somnath M.; Bagchi, Sayan (Journal of Physical Chemical Letters, 2014)
Hydrogen-bonding plays a fundamental role in the structure, function, and dynamics of various chemical and biological systems. Understanding the physical nature of interactions and the role of electrostatics in hydrogen-bonding has been the focus of several theoretical and computational research. We present an experimental approach involving IR-C-13 NMR correlations to determine the electrostatic nature of carbonyl hydrogen-bonding interactions. This report provides a direct experimental evidence of the classical nature of hydrogen-bonding interaction in carbonyls, independent of any theoretical approximation. These results have important implications in chemistry and biology and can be applied to probe the reaction mechanisms involving carbonyl activation/stabilization by hydrogen bonds using spectroscopic techniques.

Electrostatic interactions are key to C=O n-pi* shifts: an experimental proof - Haldar, Tapas; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2016)
Carbonyl n-pi* transitions are known to undergo blue shift in polar and hydrogen-bonding solvents. Using semiempirical expressions, previous studies hypothesized several factors like change in dipole moment and hydrogen-bond strength upon excitation to cause the blue shift. Theoretically, ground-state electrostatics has been predicted to be the key to the observed shifts, however, an experimental proof has been lacking. Our experimental results demonstrate a consistent linear correlation between IR (ground-state phenomenon) and n-pi* frequency shifts (involves both ground and excited electronic-states) of carbonyls in hydrogen-bonded and non-hydrogen-bonded environments. The carbonyl hydrogen-bonding status is experimentally verified from deviation in n-pi*/fluorescence correlation. The IR/n-pi* correlation validates the key role of electrostatic stabilization of the ground state toward n-pi* shifts and demonstrates the electrostatic nature of carbonyl hydrogen bonds. n-pi* shifts show linear sensitivity to calculated electrostatic fields on carbonyls. Our results portray the potential for n-pi* absorption to estimate local polarity in biomolecules and to probe chemical reactions involving carbonyl activation/stabilization.

Electrostatic manifestation of micro-heterogeneous solvation structures in deep-eutectic solvents: a spectroscopic approach - Chatterjee, Srijan; Haldar, Tapas; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry B, 2020)
Deep eutectic solvents have emerged as inexpensive green alternatives to conventional solvents for diverse applications in chemistry and biology. Despite their importance as useful media in various applications, little is known about the microscopic solvation structures of deep eutectic solvents around solutes. Herein, we show that the electrostatic field, which can be estimated both from infrared experiments and theory, can act as a unified concept to report on the microscopic heterogeneous solvation of deep eutectic solvents. Using a fluorophore containing the carbonyl moiety as the solute and the electrostatic field as a descriptor of the solvation structure of the deep eutectic solvents, we report the residue-specific distribution, orientation, and hydrogen bonding in deep eutectic solvents constituting of choline chloride and alcohols of varying chain-lengths. We observe that an increase in alcohol chain-length not only affects the alcohol's propensity to form hydrogen bond to the solute but also alters the spatial arrangement of choline cations around the solute, thereby leading to a microheterogeneity in the solvation structure. Moreover, to extend our electrostatic field based strategy to other deep eutectic solvents, we report an emission spectroscopy based method. We show that this method can be applied, in general, to all deep eutectic solvents, irrespective of their constituents. Overall, this work integrates experiments with molecular dynamics simulations to provide insights into the heterogeneous DES solvation.

Evidence of an nN(amide) → π*Ar interaction in N-Alkyl-N,N′-diacylhydrazines - Deka, Jugal Kishore Rai; Sahariah, Biswajit; Sakpal, Sushil S.; Bar, Arun Kumar; Bagchi, Sayan; Sarma, Bani Kanta (Organic letters, 2021)
1,2-Dibenzoyl-1-tert-butylhydrazine (RH-5849) and related N-alkyl-N,N′-diacylhydrazines are environmentally benign insect growth regulators. Herein, we show that an unusual n<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">N(amide) → π*<span style="outline: none; font-size: 12.75px; line-height: 0; position: relative; bottom: -0.25em; font-family: Georgia, serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; background-color: rgb(244, 244, 244);">Ar interaction mediated by a hydrazide amide nitrogen atom plays a crucial role in stabilizing their biologically active trans–cis (t–c) rotameric conformations. We provide NMR and IR spectroscopic evidence for the presence of these interactions, which is also supported by X-ray crystallographic and computational studies.